Kajian kualitas air dan kondisi sanitasi sumur gali di Lingkungan Permukiman Kelurahan Kampung Bugis, Kota Tanjungpinang - Arizki, Elita Putri Frisma; Simbolon, Veronika Amelia; Daswito, Rinaldi (TROPHICO, 2025)
The use of protected dug wells in Tanjungpinang City reached 29.84%, while the use of unprotected dug wells in the community reached 1.40%. At the research location, it was found that the distance to the source of contamination (septic tank) was less than 15 meters, did not have a cover, buckets and rope were placed on the floor of the well, allowing contamination. The purpose of the study was to determine the description of water quality and sanitation of dug wells in Kampung Sei Nyirih RT 002 RW 005 Kelurahan Kampung Bugis. This type of research was descriptive with a total of 20 samples (physical, chemical, microbiological, and sanitation of dug wells). The research instruments used TDS meter, pH meter, Dry Compact EC, and checklist sheet. Univariate analysis was used in this study. A total of 15% of samples did not meet odor, color, and taste requirements. Examination of water chemical quality as many as 60% of samples did not meet the requirements of the pH parameter of clean water. In the E. Coli parameter, 100% of the samples did not meet the requirements. The results of the sanitary inspection of dug wells showed that 5% of wells were very high risk, 55% of wells were high risk, 30% of wells were medium risk, and 10% of wells were low risk. It is expected that the community in the research location to pay more attention to sanitary conditions, physical quality of water, construction of clean water sources, namely dug wells, and cooking to boil clean water sources that will be consumed